Corporate governance structure and performance of Malaysian listed companies - Tan, Wan Chin (2015)
Corporate governance plays an important role in protecting shareholders' interest. Securities Commission Malaysia has consistently revised the Malaysian Code of Corporate Governance to improve the corporate governance in all companies. Most of the principles and recommendations in Malaysia Code of Corporate Governance were largely derived from recommendations in developed countries. It is time to explore whether the various best practices and recommendations have influence on performance of Malaysian listed companies. In order to examine the influence of corporate governance variables, the linear regression was performed by focusing on board characteristic, chief executive officer duality, shareholding structure and directors' shareholding structure of 75 companies listed in Main Market under Bursa Malaysia from 2009 to 2013. The analysis results revealed a significant relationship between corporate governance variables (board size, chief executive officer duality, composition of non-executive directors, composition of directors with multiple directorships and concentrated shareholdings) and performance of the company when using market measure (Tobin's Q ratio). However, the findings revealed that only board size and concentrated shareholding had significant relationship with performance when using accounting measure (return on assets). In a nutshell, the mixed results show Malaysian companies are more concerns on future performance and growth opportunities which reflect in share price